ANALISIS PENYELENGGARAAN SISTEM INFORMASI PEMERINTAHAN DAERAH KOTA MAKASSAR SEBAGAI UPAYA PEMBERANTASAN TINDAK PIDANA KORUPSI - haeranah haeranah (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2023)
This research aims to examine the implementation of the Regional Government Information System (SIPD) and its urgency as an effort to eradicate criminal acts of corruption in the government in Makassar City. This research uses a qualitative descriptive method that examines the implementation of the Regional Development Information System through library research. Data was collected from documentation in the form of journals, research reports and government documents related to the implementation of the Regional Development Information System. The research results show that there are many things that still need to be improved in perfecting SIPD as a general application at the regional level, such as: 1) harmonization of regulations and policies, 2) synchronization of data and information content between levels of Regional Government (Regency/City/Province) and between Regional Governments with the Central Government; 3) business processes of planning, budgeting, implementation, monitoring, reporting and evaluation in regional government. regions, future improvements to SIPD must of course be in line with the National SPBE Architecture, so that the dream of implementing an Electronic-Based Government System as part of efforts to prevent corruption can be realized. Commitment to every element of the country is needed to improve the understanding that has been formed so far. The integration of these four elements in forming an anti-corruption culture can increase anti-corruption understanding and behaviour